PEKAN PEDULI KESEHATAN KELUARGA OLEH SEKOLAH TINGGI TEOLOGI TABGHA BATAM PADA HARI ULANG TAHUN YANG KE 2 YAYASAN CAHAYA OBOR BERKAT BERSAMA MASYARAKAT KOTA BATAM - Sanjay Nadeak; Pranada; Bernard Pasaribu; Dwi Glady; Ray Maharana (JURNAL BEATITUDES, 2023)
In this world no one wants to be sick. When the body is in pain, the body will feel uncomfortable. Caring for the health of the body is one of the important things that we must always strive for. Body health is the most important thing for us to maintain because the body is the main capital for carrying out daily activities. If our body is in pain, everything will feel uncomfortable. Whether sleeping, sitting, eating will never feel comfortable. Everything will feel wrong when our body's health is in a state of decline. Our body is likened to a machine where if one component is damaged it will affect all parts. The health of the human body is when the condition of the body works perfectly. It's like a machine, no matter how small a part of our body hurts, it will definitely make other organs uncomfortable. The health of our body is the main capital to get through the day and achieve success. A success in life will be in vain if we achieve it in sickness. Success will feel complete if we are in good health and we can enjoy our hard work so far. As an educational institution, we also see that health is one of the most important things for the community because if the body is healthy, education knowledge will be easily absorbed and applied, so with social service, caring for public health is part of the form of concern from Tabgha Batam Theological High School for health itself.